Persepsi & Strategi Orang Tua dalam Pengendalian Screen Time pada Anak yang Bermain Gawai - Anis Andina; Arina Rafadina; Fanny Zaskia Ramadhani; Yolanda Agustina Sihombing; Yolanda Manalu (Veritas: Jurnal Penalaran dan Riset Mahasiswa Pendidikan, 2026)
The rapid advancement of digital technology has made gadgets an inseparable part of early childhood daily life. This study aims to examine parents’ perceptions and strategies in controlling screen time among children who use digital devices. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with parents who have children using digital devices, selected using purposive sampling. The results show that most parents understand screen time only as the duration of device use, without considering the quality aspects such as content type and children’s interaction with digital media. In general, parents perceive digital device use as beneficial for learning and entertainment, but they are also aware of its negative impacts, such as addiction, emotional problems, reduced social interaction, and decreased physical activity. In practice, children are still given access to digital devices despite these concerns. The strategies applied by parents include time limitation, scheduling, supervision, and content selection, but these are not implemented consistently. Therefore, screen time control among children has not been optimal and requires more active parental involvement. It is recommended that parents not only limit the duration of use but also pay attention to the quality of content and be more consistent in accompanying their children.